Cryptococcal meningitis following umbilical cord blood transplantation, association between the occurrence of cryptococcal infection and tacrolimus discontinuation among allogeneic hematopoietic stem cell recipients. Issue 4 (April 2019) - Mitsuki, Takashi; Kimura, Muneyoshi; Araoka, Hideki; Kageyama, Kosei; Takagi, Shinsuke; Yamamoto, Go; Nakamura, Shigeki; Miyazaki, Yoshitsugu; Uchida, Naoyuki; Yoneyama, Akiko; Taniguchi, Shuichi
Abstract: Few cases of cryptococcal infection following umbilical cord blood transplantation (UCBT) have been reported. We report a case, where cryptococcal infection occurred soon after rapidly reducing the dose of tacrolimus in a UCBT recipient who received micafungin prophylaxis during the early phase of transplantation. The etiology of cryptococcal infection following allogeneic hematopoietic stem cell transplantation (allo-HSCT), including UCBT, might be associated with rapid dose-reduction of calcineurin inhibitors, such as tacrolimus during early phase of allo-HSCT. To our knowledge, this is the first English-language report to describe in detail a case of cryptococcal meningitis with fungemia during early phase of UCBT.